Overcoming self-confidence of Islamic religious education students: The influence of personal learning model - Hamzah Hamzah; Desi Sukenti; Syahraini Tambak; Wisudatul Ummi Tanjung (Journal of Education and Learning (EduLearn), 2020)
Research on student confidence has been done a lot, but the focus in the field of personal learning models has not been found. This study aimed to determine the strengthening of personal learning models in developing student self-confidence. A total of 688 students were recruited as research samples using questionnaires as data collection techniques, and analyzed using simple linear regression. This research found that personal learning models can significantly develop students' self-confidence in Islamic Religious Education subjects. The personal learning model used by the teacher is quite strong in overcoming students' self-confidence in learning Islamic religious education. Predictable, if the personal learning model is maximally applied by Islamic religious education teachers in learning, to be "strong" for increase the self-confidence of students in learning Islamic religious education. This study concludes that the teacher's personal learning model can develop students' self-confidence in learning Islamic religious education. The findings of this study develop students' self-confidence theories by applying personal learning models in teacher education activities. In addition, opening a discussion room is very intense for other researchers in developing the self-confidence of students in the learning of Islamic education in schools.